Sudden unexplained death in infancy and hyperimmunization - Urquhart, G. E. D. (1971)
Serum immunoglobulin concentrations, predominantly IgM, were raised in 72% of 39 sudden infant death cases, consistent with a state of prolonged or repeated antigenic stimulation. Anti-antibody was found in cases of sudden death significantly more frequently than in ill but living control infants. It is suggested that anti-antibody might participate in fatal anaphylaxis in such cases.